Termogravimetrisk analys av olika magnetitsliger från LKAB - Hallberg, Dan (2013)
LKAB are in a process to complement the existing underground mines in Kiruna and Malmberget with satellite open pit mines to increase the total amount of ore. This work consist of a long chain of activities from prospecting to integration of the new materials in the production. One important link is to examine and estimate the mineral processing and metallurgical properties of the materials and the effect they may have on the process and the product. This work can be carried out in different scales, from micro studies via laboratory and pilot studies up to plant scale tests. In general it is initially a very small amount of material, maybe some kilograms collected from drill cores, there for is it important to have tools and methods that cover all different process areas and experimental scales. This will give the possibility to do necessary classifications of the different materials early in the development chain and thereby increase the efficiency in the working process.In this work, a method to estimate and compare the oxidation properties of different magnetite materials in micro / laboratory scale is presented. Thermo gravimetric analyse has been used to analyse the materials. There is also a method presented that discuss a way to minimise the effect caused by particle size on the results. Finally has a method to numerical present the oxidation curves been developed. This method will make it easier and contribute to a more objective study and comparability of bigger amount of sample data. Validerat; 20131014 (global_studentproject_submitter)